Students’ Thinking Processes in Solving Higher Order Thinking Skills (HOTS) Problems Based on Metacognitive Levels - Pahmi, Miptahul; Ratnaningsih, Nani; Prabawati, Mega Nur (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2026)
This study aims to describe students’ thinking processes in solving Higher Order Thinking Skills (HOTS) problems in terms of metacognitive levels among students of class XII MIPA 4 at SMA Negeri 2 Banjarsari. This research employed a qualitative descriptive approach. The subjects were 27 students classified into three metacognitive levels (high, moderate, and low) based on a metacognitive questionnaire. Five students were selected as research subjects: one with high metacognition, two with moderate, and two with low. Data were collected through HOTS written tests, a metacognitive questionnaire, and unstructured interviews, and analyzed through data reduction, data display, and conclusion drawing. The results showed that students with high metacognitive levels performed systematic higher-order thinking through planning, monitoring, and evaluation stages. Students with moderate levels were able to solve problems procedurally but showed limited monitoring and evaluation. Students with low levels experienced difficulties in planning, monitoring, and evaluating their problem-solving processes. In conclusion, metacognitive level influences the quality of students’ thinking processes in solving HOTS problems and highlights the importance of developing metacognitive skills in mathematics learning